Competing explanations for knowledge exchange: Technology sharing within the globally dispersed R&D of the multinational enterprise - Ensign, Prescott C.; Hébert, Louis (Université d'Ottawa | University of Ottawa, 2009)
This paper explores five competing theories for technological knowledge sharing within the globally dispersed R&D function of the multidivisional, multinational firm. These five broad explanations for why a knowledge transaction occurs are: (1) economic, (2) technological, (3) organizational, (4) geographic, and (5) sociological. In addition to occurrence, likelihood of knowledge exchange success prompted by various explanations is considered. Ultimately the determination of which argument—or combination of arguments—offers the greatest explanatory power for the sharing of intermediate technological knowledge may be answered empirically.
Keywords: exchange; knowledge sharing; global R&D; multinational enterprise